BOOSTING VOCABULARY RETENTION THROUGH PLAY - Ayu Putri, Evada Dwi (Universitas Samudra, 2025)
This research aims to find out how Scattergories Game increases and trains students of grade 7 memory on vocabulary at MTsS MIM Langsa during the 2024/2025 academic year and to know students perception on using scattergories game in increasing and training student memory on vocabulary. This study used a quasi-experimental design and compared the results between the experimental group taught with the Scattergories game and the control group taught with a conventional approach. Data were collected through vocabulary pre-test and post-test to measure the improvement of skills, as well as interviews to understand students' perceptions of the game used. The results of the analysis showed a significant increase in post-test scores in the experimental group (average 66.6) compared to the control group (average 51.2), with an average difference of 21 points. Statistical tests using t-test resulted in a significance value (p < 0.05), which means the null hypothesis is rejected and the Scattergories game is proven to have a real effect. The learning effectiveness value measured by Cohen's d of 1,5 indicates a strong impact on improving students' vocabulary acquisition. In addition, most students gave positive responses to the use of the game. They considered Scattergories as a fun and challenging learning tool that helps them remember new vocabulary and improve their thinking speed. Overall, the findings of this study conclude that Scattergories game is very effective as an interactive and motivating method in learning English vocabulary.